Bicuspid aortic valve repair: systematic review on long-term outcomes - Arnaoutakis, George J.; Sultan, Ibrahim; Siki, Mary; Bavaria, Joseph E. (Annals of Cardiothoracic Surgery; Vol 8, No 3 (May 01, 2019): Advanced Techniques in Aortic Valve Repair, 2019)
Background: Many patients with bicuspid aortic valve (BAV) develop aortic regurgitation but are not considered for valve repair. This is partly due to limited long term data regarding repair durability. The purpose of the review is to summarize the long-term (1 year) outcomes of BAV repair. Methods: A systematic review was performed to evaluate durability and survival following BAV repair. OVID SP versions of MEDLINE and Embase were searched using ‘aortic valve’, ‘bicuspid’, ‘repair’, ‘David’ ‘Yacoub’, ‘reimplantation’ and ‘remodeling’. Results: Initial search produced 770 abstracts, reduced to 92 full papers for review after excluding duplications and abstract review for relevance. Twenty-six studies met full inclusion criteria. BAV repair revealed low operative mortality, with excellent 5-year survival, and low freedom from reoperation. Differences in surgical technique between reimplantation and remodeling do not appear to confer protection against reintervention. Systematic assessment of cusp height and annular stabilization in some form do appear to favor improved long term durability. Leaflet calcification is associated with higher rates of reintervention. Conclusions: BAV repair is associated with acceptable long term survival. Ongoing standardized outcome assessments will further refine surgical techniques associated with excellent repair durability.